A scoping review of conventional and laser acupuncture as a modality of treatment for migraine - Chizoba ANYIMUKWU; Vinayak K. NAHAR; Sunita KAPUR; Manoj SHARMA (Journal of Health and Social Sciences)
Introduction: Migraine is a common neurological disorders that typically manifests with repeated episodes of unilateral frequent throbbing headaches. Globally, the prevalence of migraine is around 10%. Despite the wide variety of pharmacological medications, patients still experience frequent attacks or are unable to get complete relief from the prescribed medications. Conventional and laser acupuncture are alternative therapeutic treatment modalities that have been widely used for people with migraine. The purpose of this study was to review the collective evidence on the role of acupuncture in alleviating the symptoms of migraine. Methods: A scoping review of current literature was performed. The inclusion criteria for including interventions in this study were: (a) published in English language between 2013 and January 2018; (b) indexed in MEDLINE/PubMed, CINAHL, AltHealthWatch, and SCOPUS; (c) quantitative evaluations of acupuncture as a modality of treatment; (d) original, peer-reviewed research articles; and (e) utilized patients diagnosed with migraine. Results: A total of 23 interventions with a combined total of 1,714 study participants met the inclusion criteria. Findings indicate that acupuncture is a promising approach in the treatment of migraines accompanied with or without an aura. Limitations of this review included varied dosage of acupuncture among different studies, small sample sizes, and lack of behavioral theory-based approaches in promoting this modality. Discussion and Conclusion: The present evidence indicates that acupuncture may provide symptomatic relief and improvement in quality of life among migraine patients. It has a promising role as an adjuvant to conventional drug therapy. More randomized controlled trials for efficacy and effectiveness testing are needed.